Evaluation of bioprocess parameters for pilot scale fermentative biohydrogen production using organic waste: Environmental remediation, techno-economic challenges & future solutions - Srivastava N.; Singh R.; Lal B.; Haque S. (My University, 2025)
Hydrogen is regarded as clean future fuel and biological route of hydrogen production is amongst the most sustainable and pollution free alternatives. Biohydrogen production from organic waste via fermentation technology is one of the most promising approaches. Though, pilot scale frequent production of this fuel is also on trial stage and its distribution is still odd around the globe due to concern such as unavailability of substrate, incomplete conversion and poor yield. Because of these notable issues, mass scale trials results are different from lab scale trials. Therefore, for applications as an energy source, evaluation of mass-scale H2 production and analysis of different key influential factors of the process technology are mandatory for diverse applications. Thus, the goal of the present review is to explore and evaluate the important and most influential bioprocess parameters for pilot-scale biohydrogen production using organic substrates through dark fermentation. Different process parameters and their influence on pilot scale have been explored with the existing shortcomings and the possible solutions. The future possibilities in reference to pilot-scale biohydrogen production on a global scale have also been discussed, which can be helpful in implementing biohydrogen as a green energy source for a sustainable and clean environment. © 2024